The application of discord as an effort to increase students’ wellbeing in physical education learning during the COVID-19 emergency - Mashud; Warni, Herita; Arifin, Syamsul; Ferry, Muhammad; Pebriyandi; Kristiyandaru, Advendi (Journal Sport Area, 2021)
Physical education learning in high school during the current Covid-19 emergency, teachers have difficulty delivering material, controlling, evaluating, and providing learning feedback, especially on basic competencies that contain motion. The research objective was to improve students’ wellbeing in high school physical education learning during the Covid-19 emergency by implementing the disdcord application. Students’ wellbeing in this study, the researcher described three indicators of achievement, that is: 1) appropriateness of learning, 2) student satisfaction in learning, and 3) improved learning outcomes. The research method used was a pre-experimental one group pre-test post-test design. The population was the students of SMAN I Kota Banjarbaru class X totaling 8 classes. Two classes of samples were selected by random technique. The learning implementation instrument and student satisfaction with learning used a questionnaire with a likert scale, while for learning outcomes using a push-up test and sit-up test. The data analysis technique used the t-test sample paired test. The results of the study showed an increase in students’ wellbeing in terms of; 1) a significant increase in the implementation of learning seen from the value of the two-tailed difference test (2-tailed) = 0.000 < 0.05, 2) a significant increase in student satisfaction in learning seen from the two-way difference test value (2-tailed) = 0.000 < 0.05, and 3) a significant increase in student learning outcomes seen from the two-way difference test value (2-tailed) = 0.000 < 0.05. The conclusion of the research is that the application of the discord application in learning physical education in high schools during the Covid-19 emergency improves students’ wellbeing.